Dipeptidyl Peptidase-4 Inhibitors and Cardiovascular Side Effects - Rizal Rizal (Pharmaceutical Journal of Indonesia, 2021)
Aim: WHO projects that diabetes will be the seventh leading cause of death in 2030. One of the macrovascular of diabetes is cardiovascular (CV) diseases, reported incidence of heart failure in diabetic patients is twice greater than control subjects and intensive use of antidiabetic drugs in diabetic patients increase CV mortality. This review will discusses the effect of DPP4 inhibitors (DPP-4i) on CV outcomes.Data sources: PubMed 32 journals, Google Scholar 17 journals, BioMed Central 5 journals and others 1 journalMethod: A systemic search of all English-language articles up to 2020 was conducted using the following terms: dipeptidyl peptidase-4 inhibitors, sitagliptin, vildagliptin, saxagliptin, linagliptin, alogliptin, gemigliptin, anagliptin, teneligliptin, alogliptin, trelagliptin, omarigliptin, cardiovascular, and mechanism on cardiovascular diseases.Results: Positive effect on CV of DPP-4i mediated by activate PI3K, CAMP, eNOS and PKA, and negative effect because their effects in modulate SP, peptide YY, and neuropeptide Y. CV outcomes of DPP-4i versus placebo are variated for MACEs, which are reported on sitagliptin HR 0.98, 95% CI 0.89 to 1.08; Vildagliptin RR 0.82, 95% CI 0.61 to 1.11; Saxagliptin HR 1.00, 95% CI, 0.89 to 1.12; LinagliptinÂ  HR 0.78, 95% CI, 0.55 to 1.12; Alogliptin HR 0.85, CI 95%, 0.66 to 1.10; and Omarigliptin HR=0.85, CI 95%, 0.66-1.10.Conclusion: Based on the mechanism DPP-4i inhibitors have either cardioprotective actions or poorer outcomes on CV because their activities are connected with the inhibition of various substrates. DPP-4i sitagliptin, vildagliptin, saxagliptin, linagliptin, alogliptin, and omarigliptin did not significantly increase of MACE (major adverse cardiac events).